A Summary Assessment of Innovativeness of The New Member States of The European Union - Dworak, Edyta; Grzelak, Maria Magdalena (Comparative Economic Research. Central and Eastern Europe, 2017)
This paper attempts to assess the level of innovativeness of the economies of the ‘new’ EU member states1 in the years 2008–2015, with particular attention paid to the position of the Polish economy. This assessment was carried out on the basis of a summary index constructed with the use of statistical methods of linear ordering. The paper also presents conclusions from the analysis of the evolution of selected factors characterizing the innovativeness of the new EU member states. In the conducted analysis, statistical data from Eurostat were used to describe the innovativeness of economies with respect to two areas: (a) science and technology; and (b) education and training. The developed ranking of innovativeness of the new EU Member States, built on the basis of a summary index, makes it possible to state that the countries with the highest level of innovativeness among 13 analyzed countries were Slovenia, the Czech Republic and Malta. Poland’s above‑average value of the summary index for these countries occupied sixth position in the ranking, which indicates a relatively low level of innovativeness of the Polish economy.